Outpatient dental procedures carried out by Pediatric Dentists within Brazil's public healthcare system - Ricardo Barbosa LIMA; Ana Paula Gomes e MOURA; Paulo NELSON-FILHO; Léa Assed Bezerra da SILVA; Marília Pacífico LUCISANO; Raquel Assed Bezerra da SILVA (Sociedade Brasileira de Pesquisa Odontológica, 2024)
Abstract Brazil's public healthcare system (SUS) offers specialized oral health services to Brazilians, but the productivity of specialists, such as Pediatric Dentists, has not been characterized. Therefore, the objective of this study was to characterize the outpatient dental procedures (ODPs) carried out by Pediatric Dentists within the SUS. An epidemiological study with an ecological, longitudinal, retrospective, and quantitative approach was conducted. The ODPs carried out by Pediatric Dentists within the SUS were characterized based on type of procedure, complexity level, and circumstance (urgent or elective). Data were analyzed using a descriptive and analytical approach, considering a significance level of 5%, as well as the impact of the COVID-19 pandemic (the 2020-2022 years were not included in secondary analyses). In the last 15 years, 29,234,972 ODPs were carried out by Pediatric Dentists within the SUS. Clinical procedures were the majority (55.4%), significantly more frequent than all other types of procedures (all p <0.05). Among these, restorative and periodontal procedures were the most common (30.7% and 21.0%, respectively). From 2008 to 2019, excluding COVID-19 pandemic years, the trend over the last 15 years was constant for all types of procedures (all p >0.05). In addition, low complexity ODPs were the majority (90.1%), significantly more frequent than medium (9.7%) and high complexity procedures (0.1%) (both p <0.05). At last, most ODPs were not characterized by circumstance in the outpatient production reports (96.9%). Therefore, it was possible to conclude that Pediatric Dentists carried out diverse ODPs within the SUS over the past 15 years, although there was a dominant pattern of type and complexity.